2010
DOI: 10.1007/s00284-010-9599-0
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Vibrio parahaemolyticus and Its Specific Phages from Shrimp Ponds in East Coast of India

Abstract: Vibrio parahaemolyticus is a natural microflora of marine and coastal water bodies and associated with mortality of larval shrimp in penaeid shrimp in ponds. Bacteriophages occur virtually in all places where their hosts exist. In this study, total distribution of V. parahaemolyticus and its phages were examined in shrimp ponds, seawater, estuary, animal surface, and tissues. Total vibrio count in sediments of two ponds was found to be 2.6 × 10(3) and 5.6 × 10(3) cfu/g. Incidence of V. parahaemolyticus in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 32 publications
2
22
0
1
Order By: Relevance
“…Our results suggested that phages can be found in virtually all places where their related hosts exist. Several other investigations reported the presence of Vibrio-specific lytic phages in environmental water (shrimp ponds, aquaculture system, sea water and aquatic product market) from different regions of the world (Alagappan et al, 2010;Luo et al, 2016;Stalin and Srinivasan, 2016;Katharios et al, 2017;Srinivasan and Ramasamy, 2017;Yang M. et al, 2019).…”
Section: Origin and Morphology Of Phages Ba3 And Ca8mentioning
confidence: 99%
“…Our results suggested that phages can be found in virtually all places where their related hosts exist. Several other investigations reported the presence of Vibrio-specific lytic phages in environmental water (shrimp ponds, aquaculture system, sea water and aquatic product market) from different regions of the world (Alagappan et al, 2010;Luo et al, 2016;Stalin and Srinivasan, 2016;Katharios et al, 2017;Srinivasan and Ramasamy, 2017;Yang M. et al, 2019).…”
Section: Origin and Morphology Of Phages Ba3 And Ca8mentioning
confidence: 99%
“…Bacteriophages are viruses that naturally occur in all places where bacteria are found, they are often isolated from the same culture ponds, are considered environmentally friendly (Alagappan, Deivasigamani, Somasundaram & Kumaran, ), and are generally characterized by their narrow host range allowing no other bacteria be infected (Oliveira, Castilho, Cunha & Pereira, ). However, their high specificity at strain level, rather than at specie level, limits the application against highly diverse bacterial variants, such as VPMS1 phage.…”
Section: Lytic Effect Of Vpms1 Phage and Muralytic Activity Of Endolymentioning
confidence: 99%
“…Alagappan et al . () isolated eight bacteriophages (V1, V3–V6, V9, V11 and V12) from V. parahaemolyticus strains MTCC‐451, which were associated with healthy shrimp ( P. monodon ) and shrimp culture ponds (water and sediment samples). All phages were able to infect V. parahaemolyticus (strains V1, V3–V6, V9, V11, V12 and MTCC), but only phage Vp1 was able to lyse all the isolated V. parahaemolyticus strains tested.…”
Section: Phages Against Bacteria Causing Ahpndmentioning
confidence: 99%